Reducing plug flow effect on measured rheological results of cement-based materials: Image analysis and numerical iteration approach - Xu, Zhisong; Sun, Wen; Liu, Jiaping (Construction & building materials, 2024)
The rheological properties of cement-based materials (CBM) significantly influence their workability and application in construction. Despite the common use of coaxial cylinder rheometers for measuring these properties, challenges arise, particularly at low shear rates due to plug flow within the tested samples. This study aims to investigate the impact of plug flow on rheological property measurements of CBM and proposes strategies to enhance measurement accuracy. An image analysis method and a novel numerical iteration algorithm were proposed in this study to address plug flow effects. Three series fresh cement paste with different fluidities were prepared to conduct the rheological tests. Through the image analysis method, actual shear radii at different rotor speeds were measured. The corresponding rheological parameters were determined and compared using the complete shear assumption, the image analysis method, and numerical iteration algorithm, respectively. The results indicated the great influence of plug flow on rheological results, especially at low shear rates and low fluidities, highlighting the need for its consideration in rheological parameters calculations. Moreover, the proposed numerical iteration algorithm was verified to calculate the incomplete shear state of CBM and improve the measurement accuracy of rheological parameters. The extensions and limitations of the numerical iteration algorithm in its application were discussed further. •Rheology tests of cement paste were conducted using a coaxial cylinder rheometer.•An image analysis method was provided to measure actual shear radii in rheometer.•A numerical iteration approach was developed to enhance measured rheology accuracy.•The influences of plug flow on the measured rheological results were investigated.•The extensions and limitations of the numerical iteration approach were discussed.